Effects of Continuous or End-of-Day Far-Red Light on Tomato Plant Growth, Morphology, Light Absorption, and Fruit Production - Kalaitzoglou, Pavlos; van Ieperen, Wim; Harbinson, Jeremy; van der Meer, Maarten; Martinakos, Stavros; Weerheim, Kees; Nicole, Celine C. S.; Marcelis, Leo F. M. (Frontiers in Plant Science, 2019)
Shading by sunlit leaves causes a low red (R) to far-red (FR) ratio that results in a low phytochrome stationary state (PSS). A low PSS induces an array of shade avoidance responses that influence plant architecture and development. It has often been suggested that this architectural response is advantageous for plant growth due to its positive effect on light interception. In contrast to sunlight, artificial light sources such as LEDs often lack FR, resulting in a PSS value higher than solar light (~0.70). The aim of this study was to investigate how PSS values higher than solar radiation influence the growth and development of tomato plants. Additionally, we investigated whether a short period of FR at the end of the day (EOD-FR) could counteract any potentially negative effects caused by a lack of FR during the day. Tomato plants were grown at four PSS levels (0.70, 0.73, 0.80, and 0.88), or with a 15-minute end-of-day far-red (EOD-FR) application (PSS 0.10). Photosynthetic Active Radiation (PAR; 150 mol m-2 s-1) was supplied using red and blue (95/5%) LEDs. In an additional experiment, the same treatments were applied to plants receiving supplementary low-intensity solar light. Increasing PSS above solar PSS resulted in increased plant height. Leaf area and plant dry mass were lower in the treatments completely lacking FR than treatments with FR. EOD-FR-treated plants responded almost similarly to plants grown without FR, except for plant height, which was increased. Simulations with a 3D-model for light absorption revealed that the increase in dry mass was mainly related to an increase in light absorption due to a higher total leaf area. Increased petiole angle and internode length had a negative influence on total light absorption. Additionally, the treatments without FR and the EOD-FR showed strongly reduced fruit production due to reduced fruit growth associated with reduced source strength and delayed flowering. We conclude that growing tomato plants under artificial light without FR during the light period causes a range of inverse shade avoidance responses, which result in reduced plant source strength and reduced fruit production, which cannot be compensated by a simple EOD-FR treatment.